Love matters: embracing love as the heart of higher education - Imad, Mays (Frontiers in Education, 2024)
This reflective essay explores the role of love in higher education through the lens of personal experiences, including confronting situations of tragedy and hopelessness as an educator.Drawing on the philosophies of Dr. Martin Luther King Jr. and James Baldwin, as well as insights from colleagues and students, I argue that love is not simply an emotional state but a transformative force capable of effecting meaningful, sustainable change. Love can serve as a vital element in pedagogical settings, providing a framework for justice, equity, and communal wellbeing. I offer several practical recommendations for educators to intentionally cultivate a culture of love in their interactions with students and colleagues. These range from self-care and setting boundaries to integrating love into course design and community building. The essay suggests that embracing love as an active force can provide a renewed sense of purpose, particularly in times of collective trauma and uncertainty. Further, it highlights that love can be the necessary counterforce to the challenges affecting both educators and students, ultimately serving as the cornerstone for transformative education. By fostering love in academic settings, we enable both individual and communal healing, enriching the overall educational experience.In the wake of global crises like pandemics, genocides, climate disaster, and political divisiveness, the essay asserts that love remains the enduring force that can empower us to build a more just and resilient community in higher education.